Optimisation of PLA filament consumption for 3D printing using the annealing method in home environment - Djukanović, Milena (Strojniški vestnik, 2022)
The idea for this paper came with the outbreak of the Covid-19 pandemic when almost all countries started experiencing shortages of different, previously abundant, materials. As with all other communities, these shortages prompted the 3D printing community to become more involved in the global fight against the Covid-19. This fight was further facilitated by a large number of world-famous companies which provided their 3D models of protective masks, visors, and other aids to medical staff free of charge together with the recommended parameters and open-source files used for their printing. The idea of these companies was to support their countries by providing protective equipment for everyone who sorely needed it, especially at the beginning of the pandemic, but this mass 3D printing led to a shortage of 3D printing filaments. One of the main ideas behind this paper is to show that this problem can be drastically reduced by optimising filament consumption when printing those models. One way of doing this is strengthening the printed element by annealing it, which is the topic of this paper. By strengthening it afterwards, one could reduce filament consumption by reducing the infill percentage in the G code creation procedure. For this research, we opted for a polylactide acid (PLA) filament, because it is the most widely used 3D printing material. By varying its annealing temperature and time, and testing it, the results gave us an optimal procedure for strengthening the PLA prints, as well as an optimal solution for consumption reduction that would be the most suitable during material shortages. These results could be of great significance if applied globally.
Keywords: 3D printing; 3D-tisk; annealing; consumption optimisation; Covid-19; material PLA; ojačenje PLA; optimizacija porabe materiala; PLA material; PLA strengthening; žarjenje